KOORDINASI KEPALA DESA DAN BPD DALAM PEMBANGUNAN DESA DI DESA SIDAS KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Fernando Fajar E.42009055 (FISIP Universitas Tanjungpura Pontianak, 2022)
This script intend to bring the effective coordination between the head of village and BPD in the rural development at Landak Regency. The title of this script based by the issues of the relation betweet the head of village and BPD that can not harmonious especially in the establishment of APBDes at Landak Regency still can not be optimal. This research use qualitative research model by using the theory of coordination